PEMBATASAN HAK MANTAN NARAPIDANA UNTUK MENJADI APARATUR SIPIL NEGARA DIKAITKAN DENGAN HAK ASASI MANUSIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
As we have encountered in the community life, there are so many exconvictswho are not considered as even isolated in their own environment, thelaw that should be an objective of improvement and prevention of acts that are notgood in its application becomes a reversal of the law, Human Rights and theBasic Law The year 1945 seemed out of sync with the real life, which should havecreated a sense of justice, equality, and civilization. The purpose of writing thisthesis, namely: First, to find out the impact of imprisonment on the rights of exconvictsto become State Civil Apparatus. Second, to find out the appropriatenessof the limitation of the rights of ex-convicts to become a State Civil Apparatuswith Human Rights.This type of research is normative legal research, because in this study theauthors conducted research in legal synchronization, data sources used,secondary data, primary data and tertiary data, data collection techniques in thisstudy with the literature review method.From the research results there are two main problems that can beconcluded. First, the Impact of Criminal Enforcement on the Rights of FormerPrisoners to Become a State Civil Apparatus, If the convicted person hascommitted a crime in accordance with the sanctions given to him, then theconvicted person becomes an ordinary person / legal subject whose rights andobligations must be returned. The purpose of criminal law is the imposition ofsanctions imprisonment for violations of criminal law in order to return to being arespected member of society by carrying out imprisonment with a penal systemregulated in the Penitentiary Act. Second, the limitation of the rights of exconvictsto become the state civil apparatus is very contrary to human rights, howcan they not, whereas the rights of everyone are highly guaranteed in humanrights, human rights have been regulated in the 1945 Constitution both in thepreamble as well as its torso, affirming that every citizen is equal in law andgovernment, and must uphold the law and government with no exceptions.Keywords : Human Rights – Criminalization - Convict